Socio-Cultural Context, Environment and Conservation of Vernacular Architecture Lamin Pamung Tawai - Siela Mara Nabela; Ema Yunita Titisari; Sri Utami (Journal of Social Science, 2022)
Lamin Pamung Tawai is the vernacular house of the Dayak Kenyah tribe living on Samarinda City's outskirts. Along with the development of times and the flow of globalization, local or regional culture is displaced. This research was conducted so that there is documentation of Lamin Pamung Tawai. In addition, raising the values ​​of local wisdom contained in the construction of this vernacular house can be a lesson for academics, architects, government, and society, especially in tropical mountainous areas with unique climates, where the climate is cold but in a tropical area. This study also aims to enrich the knowledge of the archipelago vernacular houses, which the nation's ancestors wisely designed. Samarinda City is one of the big cities in East Kalimantan. So, this study is expected to be able to provide input for the construction of buildings in Samarinda City. Thus, buildings that pay attention to the ecological concepts and local wisdom of the Dayak Kenyah tribe can be created.